기업가정신교육이 대학생들의 창업의도에 미치는 영향 - 자기효능감과 창업동기의 매개효과를 중심으로 - 양준환; Yang, Jun Hwan (벤처창업연구, 2014)
A consistent agreement has been made among researchers with regards to entrepreneurship as a critical determinant in fostering and promoting start-up new businesses. Many prior studies claim that entrepreneurial education plays a significant role in facilitating and enforcing entrepreneurship among people, and consequently it leads to active creation of new businesses. This study examines practical effectiveness of entrepreneurial education being provided by universities for university students. The findings of the study are summarized as followings. The effect of entrepreneurial education was significantly influencing on entrepreneurial intention of university students. It also turned out entrepreneurial education delivered a significant effect on forming both entrepreneurial motivation and self-efficacy of university students. Mediating effect was appeared partially over the path between entrepreneurial education and entrepreneurial intention by self-efficacy and entrepreneurial motivation. Discussion and practical implication on the findings are addressed and provided. 본 연구는 대학에서 이루어지는 기업가정신교육의 실질적인 효과를 살펴보기 위해 진행되었다. 이에 따라 기업가정신교육이 대학생들의 창업의도 형성에 영향을 미치는가를 확인해보았다. 또한 기업가정신교육이 대학생들의 창업동기와 자기효능감의 형성에 어떠한 영향을 주는지 그리고 나아가 기업가정신교육이 궁극적으로 청년 대학생들의 창업의도 형성에 유의미한 역할을 수행하는가를 살펴보았다. 연구결과를 요약하면 다음과 같다. 첫째, 기업가정신교육은 대학생들의 창업의도에 유의한 정의 영향을 미치는 것으로 나타났다. 둘째, 기업가정신교육은 대학생들의 자기효능감과 창업동기에 유의한 정의 관계가 있는 것을 알 수 있었다. 셋째, 자기효능감과 창업동기는 대학생들의 창업의도에 유의한 정의 영향을 주는 것으로 나타났다. 넷째, 자기효능감과 창업동기는 기업가정신교육과 창업의도 사이에 유의한 부분매개역할을 하는 것을 확인할 수 있었다. 마지막으로 본 연구결과에 대한 논의 및 이론적, 실무적 시사점을 제시하였다.